Demodex spp. within the limbal dermoid – causal pathogen or an irrelevant finding? Case report - Szpura, Emilian; Rospond-Kubiak, Iwona; Marszałek, Andrzej; Kocięcki, Jarosław (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
The aim of the study is to report a case of limbal dermoid associated with infestation of Demodex species ( Demodex spp .). A 27-year-old man presented with ocular discomfort and a pink conjunctival lesion in his left eye. The lesion had been present since birth and it occassionally grew eyelashes. The tumour was located in an inferior temporal quadrant, involving approximately 1/6 of the limbal surface area. High frequency ultrasound revealed deep corneoscleral inifiltration, so a subtotal resection was performed. Histological evaluation revealed the presence of Demodex spp . in an abnormal sebaceous gland located within the tumour. Limbal dermoid might be associated with Demodex spp . infestation, if abnormal sebaceous glands are formed inside the lesion.